Spinal arteriovenous malformation in a pediatric patient with a history of congenital syphilis: a case report - Mia J. Bertoli; Kruti Parikh; David Klyde; Catherine A. Mazzola; Shridevi Pandya Shah (BMC, 2021)
Abstract Background Spinal arteriovenous malformations in children are extremely rare and pose great risk for intraoperative hemorrhage. Congenital syphilis sometimes presents with vascular symptoms, however, there is little published on patients with a history of congenital syphilis presenting with spinal arteriovenous malformations. Case presentation A 15-month-old female with a history of congenital syphilis presented with urinary retention, fever, and subacute onset of paraplegia. MRI showed a lesion at T8-L1, angiogram was performed which confirmed the presence of a complex type IVc arteriovenous malformation and fistula from Artery of Adamkiewicz at L1-L2. It also showed peri medullary dilated veins and a pseudoaneurysm that compressed the spinal cord at T8-T10. Somatosensory evoked potentials and motor-evoked potentials were not recordable on the bilateral lower extremities prior to surgery. Once the patient was optimized for surgery, osteoplastic laminotomies from T6-T12 were performed. The dura was opened and the intradural, intramesenchymal hematoma was evacuated. There were two episodes of brisk arterial bleeding with hypotension during resection of the hematoma. The patient was taken to the angiography suite from the OR to successfully coil the large aneurysm. Intraoperative spinal cord monitoring remained undetectable in the bilateral lower extremities. The patient's paraplegia remained unchanged from preoperative presentation. Conclusion Congenital syphilis may present with vascular changes that might impact surgical approaches and treatment outcomes in patients with spinal arteriovenous malformations. Preparation for massive transfusion and intraoperative monitoring are imperative in ensuring a safe perioperative experience.